Modern tactics of managing patients with pulmonary arterial hypertension associated with systemic connective tissue diseases. - O. O. Khaniukov; L. I. Vasylieva; Ye. D. Yehudina; O. S. Kalashnykova (Medičnì Perspektivi)
A review of the literature on the problem of one of the rare manifestations of systemic diseases - pulmonary arterial hypertension is presented. The necessity of early and thorough differential diagnosis, verification of the diagnosis using invasive methods for assessing central hemodynamics is substantiated. A model for screening patients with systemic scleroderma, which simplifies the determination of indications to set the research methods that allow to verify the diagnosis is proposed. Modern approaches to drug therapy are described, and questions of improving the patients’ survival with this prognostically unfavorable pathology are discussed.